The Role of the Power of the Board of Directors of a Business Entity in the Quality of Government Construction Projects: A Case Study of the Decision of the Maumere District Court Number 16/Pdt.G/2020/PN Mme - Kartiwan, Tatang; Sadino, Sadino; Shebubakar, Arina Novizas; Suprijanto, Iwan (PT Mattawang Mediatama Solution, 2024)
Based on Law No. 2 of 2017 on Construction Services and Law No. 40 of 2007 on Limited Liability Companies, as well as Presidential Regulation No. 16 of 2018 on Government Procurement of Goods/Services, construction services are an essential part of national development. However, the execution of the authority of the board of directors often becomes a critical point that affects the quality of projects, as occurred in the case of the construction of the Dormitory of the Catholic School of Philosophy St. Paulus Ledalero (Case Study of Court Decision Number 16/Pdt.G/2020/PN Mme dated December 16, 2020). The research method used is juridical-empirical, with a case study approach and interviews with relevant parties, such as the Commitment Making Officer, Head of the Work Unit, and Chairperson of the Advocacy Team. The research findings indicate that existing regulations still have weaknesses in terms of supervision and law enforcement, which negatively impacts the quality and standards of work. It is concluded that a more comprehensive and adaptive regulatory reform is needed, including the establishment of strict criteria for the recipients of authority, as well as more effective supervision and law enforcement mechanisms to address the challenges faced in government construction service procurement.